EVALUATION OF THE PREVENTIVE EFFECTS OF CIRRHOSIS OF AN XOA PLANT EXTRACT (Helicteres hirsuta Lour) IN EXPERIMENTAL ANIMALS - Hoang Đac , Thang; Nguyen Thong , Phan; Truong Thi Thu , Hien; Hoang Le Tuan , Anh; Hoang Anh , Tuan; Tran Van , Tung; Nguyen Thanh , Binh; Le Quoc , Toan (Tạp chí Y Dược Thực hành 175, 2024)
Objective: To evaluate the prophylactic effects of cirrhosis of Helicteres hirsuta Lour (HHW) in experimental animals. Subjects and methods: White rats were divided into four groups, each with 10 rats. Group 1: the control group drank distilled water at 10 ml/kg body weight per day. Groups 2, 3, and 4 were subcutaneously injected with CCl4 dissolved in olive oil twice a week for 12 weeks to induce cirrhosis. Group 2: (CCl4 group) drank distilled water at 10 ml/kg body weight per day. Group 3: (Silymarin group) drank silymarin at a dose of 0.2 g/kg body weight per day. Group 4: (HHW group) drank HHW at a dose of 1.3 g/kg body weight per day. Results: The activities of AST, ALT, and GGT in the Silymarin and HHW groups were significantly lower than in the CCl4 group, with p < 0.001 and p < 0.05, respectively. Histopathological images showed that 7/10 rats in the CCl4 group developed F4 stage cirrhosis, while in the Silymarin and HHW groups, only 2/10 rats, the majority of rats had liver fibrosis at stages F2 and F3. Conclusion: HHW at a dose of 1.3 g/kg body weight had the effect of hepatoprotective against liver fibrosis caused by CCl4 in white rats.